Kajian Teoretik Penelitian Khotbah - Andreas Rudy Hartono (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The essence of the sermon must be interpreted in terms of the true meaning and understanding of the sermon itself. The contents of the sermon may go hand in hand with the discrepancy with the true meaning of the sermon. This needs to be criticized theologically and practically so that anyone who delivers a sermon cannot be separated from the truth that has been standardized in God's Word. In the development of science and technology, the "spewing" of the science of preaching focuses more on the results of sermons that are considered good according to the "listener" than their preparation. While the listener's understanding and understanding of the preparation of a good and right sermon is not the main consideration. Sermon listeners only judge the results and not the process of the sermon delivered. The research method used is a descriptive qualitative method with a literature study approach (library research). Thus, the author wants to contribute in the form of this research so that it can provide input for preachers to be more accountable in preparing their sermons. AbstrakEsensi khotbah harus diinterpretasikan dalam pengertian serta pemahaman yang benar dari khotbah itu sendiri. Muatan-muatan khotbah bisa saja berjalan seiring dengan ketidak sesuaian dengan makna khotbah yang benar. Hal ini perlu dikritisi secara teologis praktis, sehingga siapapun yang menyampaikan khotbah, tidak terlepas dari kebenaran yang sudah dibakukan dalam Firman Tuhan. Dalam perkembangan ilmu pengetahuan dan teknologi, “pengkarbitan” ilmu berkhotbah itu lebih menfokuskan hasil khotbah yang dianggap bagus menurut “pendengar” dari pada persiapaannya. Sementara pemahaman dan pengertian pendengar mengenai persiapan khotbah yang baik dan benar itu bukan menjadi pertimbangan yang utama. Pendengar khotbah hanya menilai hasil dan bukan proses dari khotbah yang disampaikan. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dengan pendekatan studi literatur (library research). Dengan demikian, penulis ingin memberikan sumbangsih dalam bentuk penelitian ini agar bisa memberi masukkan bagi pengkhotbah untuk lebih dipertanggungjawabkan dalam mempersiapkan khotbah-khotbahnya.